European Social Science History Conference (2020) – online (Lejda, Niderlandy), 24–27 marca 2021 r. - Gochna, Michał (Studia Geohistorica, 2022)
European Social Science History Conference (2020) – online (Lejda, Niderlandy), 24–27 marca 2021 r.